“Contribuição à geologia, petrografia e geoquímica dos diques máficos da porção centro leste de Rondônia – sudoeste do Cráton Amazônico” - Trindade Netto, Gil Barreto (2015)
Two types of mafic dykes occur in the central eastern portion of Rondônia State, In the SW Amazonian Craton. They are located at the interface between two geochronological provinces and distinct tectonic terrains (Rio Negro Juruena and Sunsas Aguapei Provinces, and Jamari Terrain and Nova Brasilandia Terrain, respectively) and are separated by the Pimento Bueno Paleozoic graben. They are named diabase I and diabase II. Diabase I trends predominantly WNW-ESE, and subordinately NW-SE, and crosscut Proterozoic rocks from Migrantopolis and Terra Boa Formations and from the Intrusive Suite of Serra da Providência. Diabase II is more widespread in the region and trends mainly N-S and NNE-SSW, and subordinately WSW-ESE. This swarm crosscuts both Proterozoic (Migrantinópolis and Terra Boa Formations), and Paleozoic rocks (Pedra Redonda and Pimenta Bueno Formations). The main petrographic differences refers to the presence of orthopyroxene only in the diabase II samples, and different textures, predominately equigranular in diabase II, and frequently porphyritic and microporphyritic in diabase I. Geochemically both types are classified as tholeiitic basalts. Diabase I (mg# 0.35-0.71) is more enriched in FeO, TiO2, K2O, P2O5 and in incompatible elements in comparison with diabase II (mg# 0.40-0.60). The difference between enrichment degree of both melts and the clear distinction between incompatible element ratios indicate that diabase I and diabase II originate from different progenitor mantles. The great similarity between the means and ranges of incompatible element ratios of diabase I dykes, Rb/Sr (0.03-0.39), K/Nb (197.42 – 1273.92), La/Nb (0.73 – 3.55), P/Nb (42.54 – 272.13), Ce/Zr (0.21 – 0.41), Ce/Yb (11.12 – 21.22), La/Yb (4.91 – 9.56), Zr/Th (61.05 – 140.54), Nb/Hf (1.34 – 7.48), Ce/Ta (36.20 – 199.65), Ba/Sr (0.65 – 2.15), Zr/Ti (75.85 – 203.08), Zr/Y (3.70 – 6.17) and metagabbros from the Nova Brasilândia Group (1.10 Ga), Rb/Sr (0.05-0.26), K/Nb (340.35 – 1304.49), La/Nb (1.68 – 3.23), P/Nb (74.20 – 264.74), Ce/Zr (0.19 – 0.67), Ce/Yb (7.04 – 57.85), La/Yb (2.86 – 25.23), Zr/Th (19.91 – 162.34), Nb/Hf (1.05 – 10.52), Ce/Ta (66.74 – 134.23), Ba/Sr (0.71 – 3.21), Zr/Ti (109.74 – 261.71), Zr/Y (2.96 – 6.16) suggest that both melts originate from similar sources, and forthcoming researches should take into account the possibility of similar intrusion ages. The geological setting of the diabase II swarm suggests that these intrusions could be Mesozoic, since intrude in Paleozoic units. Geologic and geochemical data indicate an intracontinental setting for both swarms